Evaluation of building performance using artificial neural network: study on service life planning in achieving sustainability - Yatim, J. M.; Tapsir, Siti Hamisah; Usman, F. (2007)
Construction process has often been described as a highly complex because of the number of disciplines involved from conceptual and design to construction stage. Once completed, the environmental change and usage of the building test the quality of the design and workmanship as well as the suitability of material used. The degradation of buildings are influenced by a whole set of factors such as environmental degradation agents, quality of material, protective treatment, design of buildings, quality of work and maintenance. This paper describes the global issue of sustainability, data collection and potential applications of an analysis using artificial neural network in predicting service life for an ongoing research on affordable quality housing at Universiti Teknologi Malaysia